2022
DOI: 10.1021/acs.jctc.2c00064
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Optical Pump-Resonant X-ray Probe Spectroscopy of 4-Thiouracil: A Simulation Study

Abstract: We theoretically monitor the photoinduced ππ* → nπ* internal conversion process in 4-thiouracil (4TU), triggered by an optical pump. The elementsensitive spectroscopic signatures are recorded by a resonant X-ray probe tuned to the sulfur, oxygen, or nitrogen K-edge. We employ high-level electronic structure methods optimized for core-excited electronic structure calculation combined with quantum nuclear wavepacket dynamics computed on two relevant nuclear modes, fully accounting for their quantum nature of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…The central frequency was chosen to maximize the signal strength by maximizing the polarizability cross section while still staying offresonant (pre-resonant) 53 . Otherwise the populations will contribute and dominate the coherences 54,55 . The signal is finite only when there is an overlap of nuclear wavepackets in different electronic states, making this technique free from population background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The central frequency was chosen to maximize the signal strength by maximizing the polarizability cross section while still staying offresonant (pre-resonant) 53 . Otherwise the populations will contribute and dominate the coherences 54,55 . The signal is finite only when there is an overlap of nuclear wavepackets in different electronic states, making this technique free from population background.…”
Section: Resultsmentioning
confidence: 99%
“…53 Otherwise the populations will contribute and dominate the coherences. 54,55 The signal is nite only when there is an overlap of nuclear wavepackets in different electronic states, making this technique free from population background. A single broadband pulse with the same central frequency and bandwidth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ATAS, in contrast, is dominated by population terms. This allows one to track the evolution of the electronic states with the unique advantages of XUV and X-ray sources, such as excellent temporal resolution and sensitivity to optically dark valence states due to different selection rules of core-excited states. , At the same time, we have shown that the weaker modulations in the signal due to the coherences can be highlighted in ATAS, e.g., by computing a FROG spectrogram.…”
Section: Discussionmentioning
confidence: 82%
“…Multiple off-resonant stimulated Raman methods have been proposed to study coherence present in a molecule. [81][82][83][84] In a stimulated Raman process, two temporally overlapping pulses are used as a probe that creates a Raman transition between two electronic states. One of these stimulated Raman spectroscopic methods is TRUECARS, 51 which detects the occurrence of CI by relying on the generated electronic coherence near a CI.…”
Section: Truecarsmentioning
confidence: 99%